Prevalence of MTHFR C677T polymorphism and its association with serum homocysteine and blood pressure among different ethnic groups: insights from a cohort study of Nepal - Rajendra Dev Bhatt; Biraj Man Karmacharya; Archana Shrestha; Dinesh Timalsena; Surendra Madhup; Rajesh Shahi; Nishan Katuwal; Rajeev Shrestha; Annette L. Fitzpatrick; Prabodh Risal (BMC Cardiovascular Disorders)
Abstract Background The risk of hypertension varies based on ethnicity, environmental factors, and genetic predispositions. Studies have reported a higher risk of cardiovascular diseases (CVD) and hypertension among the Newar ethnic groups in Nepal. However, the genetic analysis for Methylenetetrahydrofolate reductase (MTHFR C677T) gene mutations, serum homocysteine, and high-sensitivity C-reactive protein (hs-CRP) levels across different ethnicities remains unexplored. Methods Sociodemographic information and baseline data of 489 participants were obtained from the first phase of the Dhulikhel Heart Study. Preserved blood samples were analyzed for MTHFR C677T polymorphism using real-time polymerase chain reaction (TaqMan assay), and serum homocysteine was measured through immunoassay techniques. Descriptive analysis, the Hardy-Weinberg equilibrium test, and multinomial regression were performed. Results The prevalence of homozygous mutation (TT) was 19.8% in the Newar group and 12.5% in the Brahmin/Chhetri ethnicity. The highest mean value of homocysteine (19.4 µmol/L) was observed in homozygous participants, followed by the heterozygous mutant group (17.4 µmol/L). A statistically significant association (P = < 0.001) was found between homocysteine levels and blood pressure. Conclusions The Dhulikhel Heart Study reveals a significant prevalence of the MTHFR C677T gene mutation among the Newar ethnicity compared to other groups. Elevated levels of homocysteine and high-sensitivity C-reactive protein (hs-CRP) were associated with increased blood pressure. Clinical trial number Not applicable